Scaffold-facilitated locomotor improvement post complete spinal cord injury: Motor axon regeneration versus endogenous neuronal relay formation. (March 2019) - Li, Xing; Liu, Dingyang; Xiao, Zhifeng; Zhao, Yannan; Han, Sufang; Chen, Bing; Dai, Jianwu
Abstract: Complete transected spinal cord injury (SCI) severely influences the quality of life and mortality rates of animals and patients. In the past decade, many simple and combinatorial therapeutic treatments have been tested in improving locomotor function in animals with this extraordinarily challenging SCI. The potential mechanism for promotion of locomotor function relies either on direct motor axon regeneration through the lesion gap or indirect neuronal relay bridging to functionally reconnect transected spinal stumps. In this review, we first compare the advantages and problems of complete transection SCI animal models with other prevailing SCI models used in motor axon regeneration research. Next, we enumerate some of the popular bio-scaffolds utilized in complete SCI repair in the last decade. Then, the current state of motor axon regeneration as well as its role on locomotor improvement of animals after complete SCI is discussed. Last, the current approach of directing endogenous neuronal relays formation to achieve motor function recovery by well-designed functional bio-scaffolds implantation in complete transected SCI animals is reviewed. Although facilitating neuronal relays formation by bio-scaffolds implantation appears to be more practical and feasible than directing motor axon regeneration in promoting locomotor outcome in animals after complete SCI, there are still challenges in neuronal relays formation, maintaining and debugging for spinal cord regenerative repair.